Load Restraint with Allsafe Products. Part 1: Choosing a Semi-Trailer – A Systematic Analysis - Starkowski Dariusz (Technical Transactions, 2018)
The appropriate selection of a semi-trailer in food transport is one of the most significant factors related to management in transport companies. Two parts of the paper present research and analytical issues concerning this subject matter (second part available in: TT 2/2018). The description of this logistics problem is initiated with the proper planning of the road transport process, from consignor to recipient. Furthermore, the choice of a modern vehicle and loading system is based on the transportation of fresh strawberries. The first part of the article discusses current legal provisions existing in the European Union and Poland that concern the transport of perishable products. Moreover, the paper presents community law that concerns load restraint, and the choice of a vehicle, which is done by means of weighted-average methodology.